Efficiency of Er:YAG laser in debonding of porcelain laminate veneers by contact and non‐contact laser application modes (in vitro study). Issue 3 (11th January 2018) - ALBalkhi, Mohand; Swed, Eyad; Hamadah, Omar
Abstract: Objective: To determine the efficiency of debonding porcelain laminate veneers (PLV) by using several laser parameters and two different application modes of Er:YAG laser [contact (CM) and non‐contact (NCM)], by verification of the consumed PLV debonding time and the changes in dental pulp temperature. Materials and methods: Forty extracted non‐carious human maxillary premolars were prepared for receiving PLV. Sixteen of them were divided into two groups, each of them comprised eight samples based on the application mode; group A with NCM, and group B with CM. Veneers of both groups were debonded by the same laser parameters (360 mJ, 15 Hz) during loading of a 15 N force on specially fabricated veneer cervical margins. The primary results showed that the NCM was more efficient, thus, additional groups (C, D, and E) of the same mode and number of samples were tested with different laser parameters of energy and frequency; group C (400 mJ, 10 Hz), group D (270 mJ, 15 Hz), group E (300 mJ, 10 Hz). The failure mode was determined and classified for the debonded samples of all groups. Results: All veneers were debonded and samples of the NCM group had considerably lower debonding time (12.6 seconds) than the CM samples (96.3 seconds), however, higher changes of temperature in NCM (4.2°C) than in CM were observed (2.9°C). The failure mode of samples was either type 1 or 3. Conclusion: Er:YAG laser is an effective tool in debonding PLVs. The NCM application mode was more efficient in reducing debonding time than CM application mode but with a higher change in pulp temperature. Clinical Significance: Investigating the efficacy of Er:YAG laser as a non‐invasive particle technique for debonding of failed or malpositioned of porcelain laminated veneers